Before, proceeding to the problem, I will mention some notations on this book to be easier to read.
0. $(X, ||\, \cdot\,||)$ is Banach space
1. $L^{1}((0,T),X)$ : the space of measurable functions $u$ on $(0,T)$ with values in $X$ such that $||u||$ is integrable.
2. $D'(\Omega)$ : the space of distributions on $\Omega$.
3. $u' = u_{t} = \frac{du}{dt}$ for $u \in D'((0,T),X)$
4. $W^{1,1}((0,T),X) := \{u \in L^{1}((0,T),X),u' \in L^{1}((0,T),X), \text{in the sense of } D'((0,T),X)\}$
5. $||u||_{L^{1}((0,T),X)} = (\int_{0}^{T}||u||dt)^{1/p}$
6. $||u||_{W^{1,1}((0,T),X)} = ||u||_{L^{1}((0,T),X)} + ||u'||_{L^{1}((0,T),X)}$
7. $(D(A),||\, \cdot \,||_{D(A)})$is Banach Space with $||u||_{D(A)}= ||u|| + ||Au||$ when $A$ is a linear operator with a closed graph.
8. In this problem, $A$ is $m$-dissipative operator with dense domain and $(\mathscr{T}(t))_{t\geq 0}$ is the contraction semigroup generated by $A$.
9. $C([0,T],X)$ : space of continuous functions from $[0,T]$ to $X$.
Now, I will state the corollary.

Corollary 4.1.9
Let $x \in X$, $f \in L^{1}((0,T),X)$, and $u \in L^{1}((0,T),X)$. Assume further that $u \in L^{1}((0,T),D(A))$ or $u \in W^{1,1}((0,T),X)$. Then we have $$u(t) = \mathscr{T}(t)x + \int_{0}^{t}\mathscr{T}(t-s)f(s)ds \tag{1}$$ if and only if $u$ satisfies
(i). $u \in L^{1}((0,T),D(A))\cap W^{1,1}((0,T),X)$
(ii). $u'(t) = Au(t) + f(t)$, for almost every $t \in [0,T]$
(iii). $u(0) = x$

Before I explain the part where I do not understand, I would like to state some theorems used to prove this corollary.

Theorem (Extrapolation)
Let $X$ be Banach space and $A$ is $m$-dissipative with dense domain. Then, there exists $\bar{X}$, and $\bar{A}$ such that the Banach Space $(\bar{X},||\, \cdot\,||_{\bar{X}})$ satisfying:
(I). $X \hookrightarrow \bar{X}$ with dense embedding.
(II). $\forall x \in X, \, ||x||_{\bar{X}} = ||(I-A)^{-1}x|| \leq ||x||$
Moreover, $A$ satisfies
(I). $D(\bar{A}) = X$
(II). $\forall x \in D(A), \, \bar{A}x = Ax$
Lemma 4.1.5
$\forall x \in X, \forall f \in L^{1}((0,T),X)$, formula (1) defines a function $u\in C([0,T],X)$. In addition, we have $$\|u\|_{C([0,T],X)} \leq ||x|| + ||f||_{L^{1}((0,T),X)}$$
Now, I will state the part in which I do not understand in the textbook. So, we assume $(1)$ holds. Now, let $(f_{n})_{n\geq 0}$ be a sequence of $C([0,T],X)$ such that $f_{n} \to f$ in $L^{1}((0,T),X)$ as $n\to \infty$. Let $u_{n}$ be the corresponding solutions of (1). From Corollorary 4.7 (I understand the reasoning so I will not mention Corollorary 4.7 here) we will obtain $$\forall t \in [0,T], \, u_{n}'(t) = \bar{A}u_{n}(t) + f_{n}(t)$$ The book claims by using Lemma 4.1.5, we can show that $$u(t) = x + \int_{0}^{t}\bar{A}u(s) + f(s)ds$$ How do we get the result above by using Lemma 4.1.5? I try but to no avail using the standard $|u_n(t)-u(t)|$ trick. Any help will be much appreciated!


Recall that $$u_n(t) = \mathscr{T}(t)x + \int_{0}^{t}\mathscr{T}(t-s)f_n(s)ds\tag{1}$$ and thus $$u_n(t)-u(t)=\int_{0}^{t}\mathscr{T}(t-s)(f_n(s)-f(s))ds.$$ Therefore, from Lemma 4.1.5 applied to $u_n-u$, $$\|u_n-u\|_{C([0,T],X)} \leq \|0\| + \|f_n-f\|_{L^{1}((0,T),X)}\overset{n\to\infty}{\longrightarrow} 0$$ which implies that $$u_n(t)\overset{n\to\infty}{\longrightarrow} u(t),\quad\forall\ t\in[0,T]\tag{2}.$$

On the other hand, from $u_{n}'(t) = \bar{A}u_{n}(t) + f_{n}(t)$ it follows that $$u_{n}(t) =u_n(0)+ \int_0^t\bar{A}u_{n}(s) + f_{n}(s)\;ds \overset{(1)}{=}x+ \int_0^t\bar{A}u_{n}(s)\;ds + \int_0^tf_{n}(s)\;ds\tag{3}$$ which implies (see Remark below) that $$u_n(t)\overset{n\to\infty}{\longrightarrow} x+ \int_0^t\bar{A}u(s) + f(s)\;ds,\quad\forall\ t\in[0,T]\tag{4}.$$

From $(2)$ and $(4)$ we obtain $$u(t)=x+ \int_0^t\bar{A}u(s) + f(s)\;ds.$$

Remark. It is clear that $$\int_0^t f_{n}(s)\;ds\overset{n\to\infty}{\longrightarrow}\int_0^t f(s)\;ds\tag{5}$$ Since

  • $\bar{A}$ is closed

  • $\displaystyle\int_0^tu_{n}(s)\;ds\overset{n\to\infty}{\longrightarrow}\int_0^tu(s)\;ds$ in $X=D(\bar{A})$

  • $\displaystyle\bar{A}\int_0^tu_{n}(s)\;ds\overset{(3)}{=}u_{n}(t) -x - \int_0^t f_{n}(s)\;ds$ is convergent

we conclude that


Substituting $(5)$ and $(6)$ into $(3)$ we obtain $(4)$.

  • $\begingroup$ Thank you very much for your clear and precise explanation! Now I understand the part I did not understand previously $\endgroup$ – Evan William Chandra Oct 22 '18 at 2:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.